Badan Usaha Milik Negara (BUMN) Sebagai Termohon Pailit Dalam Kaitan Dengan Undang Undang Republik Indonesia Nomor 1 Tahun 2004 Tentang Perbendaharaan Negara - Agnest Elga Margareth; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (USU LAW JOURNAL, 2019)
Abstract. Business competitiveness today requires BUMN to be competitive with domestic and foreign private businesses. It has to innovate its products in order to be accepted by consumers and it has to have big capital to do it. Since the government does not always provide capital, BUMN has to borrow it from the third party. When it cannot pay off his debt, it has to file bankruptcy to the Court. The overlapping regulations on BUMN bankruptcy makes the third party difficult to dun the loan. The research problems are how about the legal consequence of BUMN bankruptcy on  State’s finance and on confiscation of BUMN assets according to Law No. 1/2004 on State Treasury which is in accordance with the theory of State welfare and the theory of legal entity from the aspect of purposeful wealth. The research used juridical normative with prescriptive and applied legal provision approach, using primary, secondary, tertiary legal materials. The data were analyzed qualitatively. The legal consequence of filing bankruptcy of BUMN, according to Law on State Finance, is that the State is responsible for the debt of BUMN because the State’s wealth and BUMN assets are inseparable. Confiscation can only be done on BUMN assets obtained from the State’s wealth which are sepparated, but it cannot be done on the State’s assets which are managed by BUMN because it is not in accordance with Law on BUMN, Law on State Finance, and Law onj State Treasury. This condition makes creditors difficult in filing bankruptcy and doing confiscation on BUMN which defaults.   Keywords: BUMN, bankruptcy, state finance, state treasury